UJI AKTIVITAS SISTEM SARAF PUSAT DECOCTA BATANG BROTOWALI (Tinospora Crispa (L.) Hook. f. & Thomson) PADA MENCIT PUTIH JANTAN - Selvi Merwanta; Puspa Pameswari; Ozy Maria (Jurnal Akademi Farmasi Prayoga, 2019)
Plants are raw materials that are widely used as herbal medicines. One of the plants used as herbal medicine is brotowali (Tinospora Crispa (L.) Hook. F. & Thomson) The aim of the study was to see the effectiveness of central nervous system stimulants from brotowali stem decocta in male white mice. Tests were carried out with concentrations of brotowali stem dekokta 6.5%, 13%, 26%, negative control (aquadest), and positive control (caffeine). Test parameters observed were motor activity, curiosity test, hanging test, and rotary road test. The results of the study were analyzed using Two-Way ANOVA and continued with the Duncan test. The results showed that decocta of brotowali stem with a concentration of 6.5%, 13%, 26% gave an effect on central nervous system stimulants. The smallest concentration of decocta brotowali stem that can give effect is 6.5% (close to the positive control effect (caffeine).